2022
DOI: 10.1002/jia2.25886
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality among adolescents and young adults living with HIV on antiretroviral therapy in Dar es Salaam, Tanzania: a retrospective cohort study

Abstract: Introduction: Global AIDS-related deaths have declined by only 10% among adolescents since its peak in 2003. This is disproportionately low compared to a decline of 74% among children aged 0-9 years old. We determined the magnitude of, and predictors of mortality among adolescents and young adults living with HIV on antiretroviral therapy (ART) in Dar-es-Salaam, Tanzania. Methods: A retrospective cohort study was conducted among adolescents (aged 10-19) and young adults (aged 20-24) living with HIV and enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…In addition, a meta-analysis by Belay demonstrated that TB infected children with co-infection of HIV had a higher likelihood of experiencing adverse treatment outcomes compared to HIV-negative children, about 3.2 times [53]. Regarding a single infection of HIV, a retrospective study reported a mortality rate of 2.3% among adolescents infected with HIV in Tanzania [54].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a meta-analysis by Belay demonstrated that TB infected children with co-infection of HIV had a higher likelihood of experiencing adverse treatment outcomes compared to HIV-negative children, about 3.2 times [53]. Regarding a single infection of HIV, a retrospective study reported a mortality rate of 2.3% among adolescents infected with HIV in Tanzania [54].…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that being male was a risk prognostic factor for KS-specific mortality, whereas being female was a risk prognostic factor for non-KS-specific mortality. Published studies have shown that the reasons for increased mortality observed in men living with HIV are poor health-seeking behaviour; delay in HIV status disclosure; poor access to HIV services, including testing and treatment; poor engagement with HIV services; late presentation to healthcare; delayed initiation of treatment; poor adherence to ART; and poor retention [46,47]. On the other hand, being female was associated more with non-KS-specific mortality, which might be because of earlier ART initiation avoiding HIV-related infections [48].…”
Section: Discussionmentioning
confidence: 99%
“…However, consistent with the evidence, globally, high ART uptake and VLS rates are only observed among the general population with adolescents reporting lower rates, yet adolescents account for 5% of all PLHIV [3,8]. The rates are even lower among ALHIV in sub-Sahara Africa (SSA) [1,3,911]. For instance, in 2021, VLS was only 30% among the 43% ALHIV on ART in SSA [12].…”
Section: Introductionmentioning
confidence: 90%